2012
DOI: 10.1158/1940-6207.capr-11-0412
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Levels of the APC-Interacting Protein MAPRE1, LRG1, and IGFBP2 Preceding a Diagnosis of Colorectal Cancer in Women

Abstract: Longitudinal blood collections from cohort studies provide the means to search for proteins associated with disease prior to clinical diagnosis. We investigated plasma samples from the Women’s Health Initiative (WHI) cohort to determine quantitative differences in plasma proteins between subjects subsequently diagnosed with colorectal cancer (CRC) and matched controls that remained cancer free during the period of follow-up. Proteomic analysis of WHI samples collected prior to diagnosis of CRC resulted in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 60 publications
12
82
0
Order By: Relevance
“…In our analyses, CEA was found to have higher plasma levels in colorectal cancer patients at advanced stages compared with early ones, which is consistent with previous evidence (39). Nevertheless, although CEA is limited by its poor diagnostic efficacy as a single biomarker, it could still be used in a multimarker panel to enhance the diagnostic performance, which was also seen in other studies (40,41).…”
Section: Discussionsupporting
confidence: 91%
“…In our analyses, CEA was found to have higher plasma levels in colorectal cancer patients at advanced stages compared with early ones, which is consistent with previous evidence (39). Nevertheless, although CEA is limited by its poor diagnostic efficacy as a single biomarker, it could still be used in a multimarker panel to enhance the diagnostic performance, which was also seen in other studies (40,41).…”
Section: Discussionsupporting
confidence: 91%
“…A role for LRG1 has been suggested in promoting angiogenesis through activation of the TGF-b pathway (40). Apart from PDAC, increased LRG1 plasma levels have also been found in other cancer types (41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the level of LRG1 is elevated in the sera and the tumor tissues of patients with non-small-cell lung cancer (Nakajima et al, 2011;O'Donnell et al, 2002). Similarly, the level of LRG1 has been found to be elevated in the sera of colorectal cancer patients, and is closely correlated with tumor progression (Ladd et al, 2012). Recently, Nakajima et al (2012) showed that LRG1 is distributed throughout the entire brain and is mainly expressed in the astrocytes with the expression increasing with age, suggesting a possibility of the involvement of LRG1 in astrocytic malignancy and glioma tumorigenesis.…”
Section: Introductionmentioning
confidence: 98%